Seasonal and spatial variability of surface chlorophyll inside mesoscale eddies in the South China Sea. Issue 3 (2nd July 2016) - Xiu, Peng; Guo, Mingxian; Zeng, Lili; Liu, Na; Chai, Fei
Abstract : Mesoscale eddies can influence biogeochemical cycles through both vertical nutrient or plankton flux and horizontal advection of nutrient or plankton in eddy periphery. In this study, we analyzed the seasonal and spatial variability of near-sea-surface chlorophyll- a concentrations and their corresponding modulation mechanisms by collocating satellite observations of eddies tracked during 1998–2007 in the South China Sea. We found that in winter, cyclonic eddies show significantly high chlorophyll- a in the eddy core relative to the periphery, suggesting regulation by an eddy-pumping mechanism. While in summer, chlorophyll- a values in the core of cyclonic eddies are comparable with those in the periphery, and dipole features of chlorophyll- a around cyclonic eddies are conspicuous, which is largely induced by horizontal eddy advection. For anticyclonic eddies, however, low chlorophyll- a in eddy cores compared with the periphery are consistently present over most of the year. The impact of eddy advection on chlorophyll- a distribution in anticyclonic eddies is not clear from the composite images in different seasons. Variability of chlorophyll- a to the west of the Luzon Strait and northwest of the Luzon Island demonstrate that phytoplankton biomass in these two regions is mainly controlled by an eddy-pumping mechanism. In the regions off the Vietnam coast, chlorophyll- a distributions are generally associated with horizontal eddy advection. This research highlights different mesoscale mechanisms affecting biological structures in the upper ocean, which can potentially disturb ocean biogeochemical cycling processes in the South China Sea.